Collisions with overhead wires as a cause of mortality in Mute Swans Cygnus olor - Perrins, C M; Sears, J (Wildfowl, 1991)
The ringing recoveries of Mute Swans held by the British Trust for Ornithology were analyzed for information on deaths from collisions with overhead wires. Of reported deaths, some 22% die from such a cause. This is compared with the likely actual percentage, allowing for the fact that only a proportion of dead swans are reported and that birds dying from collisions with overhead wires are more likely to be found than are birds dying from other causes. The annual patterns of deaths from collisions with overhead cables are examined in relation to the age classes of the swans involved. Not surprisingly, fewer birds die from this cause during the summer especially during those months when the birds are in moult. At other times of year, the pattern varies with the age of the bird.